Type 1 myocardial infarction in patients with acute ischemic stroke - Nolte, Christian H.; von Rennenberg, Regina; Litmeier, Simon; Leistner, David M.; Szabo, Kristina; Baumann, Stefan; Mengel, Annerose; Michalski, Dominik; Siepmann, Timo; Blankenberg, Stephan; Petzold, Gabor C.; Dichgans, Martin; et al. (JAMA neurology, 2024)
Elevated values of high-sensitivity cardiac troponin (hs-cTn) are common in patients with acute ischemic stroke and are associated with poor prognosis. However, diagnostic and therapeutic implications in patients with ischemic stroke remain unclear.To identify factors indicative of myocardial infarction (MI) in patients with acute ischemic stroke and hs-cTn elevation. The primary hypothesis was that a dynamic change of hs-cTn values (>50% change) in patients with acute ischemic stroke indicates MI.This cross-sectional study was a prospective, observational study with blinded end-point assessment conducted across 26 sites in Germany. Patients were included if they had acute ischemic stroke within 72 hours and either (1) highly elevated hs-cTn values on admission (>52 ng/L) or (2) hs-cTn levels above the upper limit of normal and a greater than 20% change at repeated measurements. Patients were enrolled between August 2018 and October 2020 and had 1 year of follow-up. Statistical analysis was performed between April 2022 and August 2023.Standardized electrocardiography, echocardiography, and coronary angiography.Diagnosis of MI as adjudicated by an independent end-point committee based on the findings of electrocardiography, echocardiography, and coronary angiography.In total, 254 patients were included. End points were adjudicated in 247 patients (median [IQR] age, 75 [66-82] years; 117 were female [47%] and 130 male [53%]). MI was present in 126 of 247 patients (51%) and classified as type 1 MI in 50 patients (20%). Dynamic change in hs-cTn value was not associated with MI in univariable (32% vs 38%; χ2﻿ P = .30) or adjusted comparison (odds ratio, 1.05; 95% CI, 0.31-3.33). The baseline absolute hs-cTn value was independently associated with type 1 MI. The best cutoffs for predicting type 1 MI were at hs-cTn values 5 to 10 times the upper limit normal.This study found that in patients with acute ischemic stroke, a dynamic change in hs-cTn values did not identify MI, underscoring that dynamic changes do not identify the underlying pathophysiological mechanism. In exploratory analyses, very high absolute hs-cTn values were associated with a diagnosis of type 1 MI. Further studies are needed how to best identify patients with stroke who should undergo coronary angiography.